Bosnia and Herzegovina : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors in Bosnia and Herzegovina. It uses International Financial Reporting Standards (IFRS), International Standards on Auditing (ISA), and the relevant portions of European Union (EU) law as benchmarks. This report shows that managers and auditors do not consistently comply with accounting and auditing requirements, which has an adverse impact on the economy. This report recommends significant changes to law and regulations to align the statutory framework with evolving internationally accepted practices, these changes include: strengthening the country's financial architecture and reducing the risk of financial market crises; contributing to foreign direct and portfolio investment and helping to mobilize domestic savings; facilitating the access of smaller-scale corporate borrowers; improving the assessment and collection of taxes on corporate profits; allowing investors to evaluate corporate prospects and make informed investment and voting decisions; allowing shareholders and the public at large to assess management performance; and facilitating Bosnia and Herzegovina's eventual integration into the European Union.